Large spin Hall angle in vanadium film - T. Wang (Nature Portfolio, 2017)
Abstract We report a large spin Hall angle observed in vanadium films sputter-grown at room temperature, which have small grain size and consist of a mixture of body centered tetragonal (bct) and body centered cubic (bcc) structures. The spin Hall angle is as large as θ V  = −0.071 ± 0.003, comparable to that of platinum, θ Pt  = 0.076 ± 0.007, and is much larger than that of bcc V film grown at 400 °C, θ V_bcc  = −0.012 ± 0.002. Similar to β-tantalum and β-tungsten, the sputter-grown V films also have a high resistivity of more than 200 μΩ∙cm. Surprisingly, the spin diffusion length is still long at 16.3 nm. This finding not only indicates that specific crystalline structure can lead to a large spin Hall effect but also suggests 3d light metals should not be ruled out in the search for materials with large spin Hall angle.